PENGARUH METODE DIGITAL STORYTELLING PROJECT BERBANTUAN PLATFORM STORYBIRD TERHADAP KEMAMPUAN MENGEMBANGKAN ALUR CERITA DALAM TEKS CERPEN SISWA KELAS XI MAN 1 KOTA PADANG - M. Taufik, Nabillah; Satria, Dadi; Rasyid, Yulianti; Indriyani, Vivi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Digital Storytelling Project method assisted by the Storybird platform on students’ ability to develop plotlines in short story texts at grade XI of MAN 1 Kota Padang. The study was motivated by students’ low ability in organizing coherent and engaging plot structures. This research employed a quantitative approach with a quasi-experimental design. The sample consisted of class XI F2 as the experimental class and class XI F7 as the control class. The research instrument was a short story writing performance test focused on plot development. Data were analyzed through normality tests, homogeneity tests, and hypothesis testing using the Independent Samples T-test. The results showed that the Digital Storytelling Project method assisted by Storybird had a significant effect on students’ ability to develop plotlines in short story texts. The use of digital visual media helped students generate ideas, organize conflicts, and construct more coherent and creative plot structures. Keywords: Digital Storytelling Project, Storybird, Plot, Short Story Text.